GENDER DIFFERENCES LEARNING VALUE: A CASE STUDY OF PLAYING MOTORCYCLE GAME LEARNING: Received: 20th October 2021; Revised: 12th February 2022, 25th February 2022, 2nd March 2022; Accepted: 03rd March 2022 - Chang, Sheng Yuan; Jan, Shiun Taung (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This study investigated the gender differences in vocational high school for playing the 3D motorcycle digital game on the tablet and the participants who don’t have the license of motorcycle driving yet. A questionnaire, relevant to the items of gameplay anxiety, cognitive anxiety, learning value and continuance intention, is conducted after playing the digital game simulated at the regulation of riding the motorcycle on the road, correctly riding behaviour and the interference with another unexcepted driving behaviour. The finding of this study is that the gender difference significantly of the gameplay anxiety, cognitive anxiety, learning value (attitude and behaviour), and the feeling of females are more than male.